Cationic Liposomes Carrying HPV16 E6-siRNA Inhibit the Proliferation, Migration, and Invasion of Cervical Cancer Cells - Luz Victoria Sánchez-Meza; Ciresthel Bello-Rios; Josimar O. Eloy; Yazmín Gómez-Gómez; Marco Antonio Leyva-Vázquez; Raquel Petrilli; María Josefa Bernad-Bernad; Alfredo Lagunas-Martínez; Luis Alberto Medina; Janeth Serrano-Bello; Jorge Organista-Nava; Berenice Illades-Aguiar (MDPI AG, 2024)
The E6 and E7 oncoproteins of high-risk types of human papillomavirus (HR-HPV) are crucial for the development of cervical cancer (CC). Small interfering RNAs (siRNAs) are explored as novel therapies that silence these oncogenes, but their clinical use is hampered by inefficient delivery systems. Modification (pegylation) with polyethylene glycol (PEG) of liposomal siRNA complexes (siRNA lipoplexes) may improve systemic stability. We studied the effect of siRNA targeting HPV16 E6, delivered via cationic liposomes (lipoplexes), on cellular processes in a cervical carcinoma cell line (CaSki) and its potential therapeutic use. Lipoplexes-PEG-HPV16 E6, composed of DOTAP, Chol, DOPE, and DSPE-PEG2000 were prepared. The results showed that pegylation (5% DSPE-PEG2000) provided stable siRNA protection, with a particle size of 86.42 ± 3.19 nm and a complexation efficiency of over 80%; the siRNA remained stable for 30 days. These lipoplexes significantly reduced HPV16 E6 protein levels and restored p53 protein expression, inhibiting carcinogenic processes such as proliferation by 25.74%, migration (95.7%), and cell invasion (97.8%) at concentrations of 20 nM, 200 nM, and 80 nM, respectively. In conclusion, cationic lipoplexes-PEG-HPV16 E6 show promise as siRNA carriers for silencing HPV16 E6 in CC.